Lista anotada de los curculionoidea (Coleoptera) de Nicaragua - Maes, J.-M.=700 1 O'Brien, Ch.W.
(En, Es)
Ilus., 110 ref.
Keywords: TAXONOMIA; CURCULIONIDAE; COLEOPTERA; DISTRIBUCION GEOGRAFICA; HUESPEDES; ENEMIGOS NATURALES; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA